2018
DOI: 10.1038/s41598-018-19697-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of low and high biofilm-forming Helicobacter pylori strains

Abstract: The biofilm-forming-capability of Helicobacter pylori has been suggested to be among factors influencing treatment outcome. However, H. pylori exhibit strain-to-strain differences in biofilm-forming-capability. Metabolomics enables the inference of spatial and temporal changes of metabolic activities during biofilm formation. Our study seeks to examine the differences in metabolome of low and high biofilm-formers using the metabolomic approach. Eight H. pylori clinical strains with different biofilm-forming-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…These possible mechanisms should be confirmed in H. pylori in a future study. These mechanisms were supported by the decrease in metabolite of the biofilm form of H. pylori compared to the planktonic strain [36]. An increasing efflux pump was also observed in biofilm-growing H. pylori [27,28].…”
Section: Discussionmentioning
confidence: 78%
“…These possible mechanisms should be confirmed in H. pylori in a future study. These mechanisms were supported by the decrease in metabolite of the biofilm form of H. pylori compared to the planktonic strain [36]. An increasing efflux pump was also observed in biofilm-growing H. pylori [27,28].…”
Section: Discussionmentioning
confidence: 78%
“…Bacterial cells in stationary biofilms have also been reported to increase synthesis of pili, fimbriae and exopolysaccharides as well as lipopolysaccharide modification and production of stress-response enzymes (Prigent-Combaret et al, 1999; Folsom et al, 2010). Wong et al recently profiled metabolites of high and low biofilm forming Hp strains from Malaysia using liquid chromatography/quadrupole time-of-flight mass spectrometry (Wong et al, 2018). The study compared four high and four low biofilm forming strains cultured up to 3 days in duplicate.…”
Section: Functional and Morphological Changes Associated With Biofilmmentioning
confidence: 99%
“…Interestingly, low-biofilm-formers produced more metabolites than high-biofilm-formers, consistent with lower overall metabolic activities in biofilm-associated bacteria. Further analysis indicated that the metabolites significantly lower in high biofilm producers belonged to major categories of lipids, with an important role in bacterial-bacterial communications, and metabolites involved in prostaglandin synthesis (Wong et al, 2018).…”
Section: Functional and Morphological Changes Associated With Biofilmmentioning
confidence: 99%
“…These variations of metabolites are attributed to the fact that the metabolome of biofilms generally changes with the maturation of biofilms (Wong et al, 2018, Singhalage et al, 2018. Polysaccharides (Jiao et al, 2010), amides (O'Toole and Kolter, 1998) and fatty acids are major components of Extracellular Polymeric Substances (EPS) of biofilms, which provide a strong and sticky framework to protect biofilms against adverse environmental conditions (Sutherland, 2001).…”
Section: Resultsmentioning
confidence: 99%